Learning Styles and Learning Strategies in College Students from Buenos Aires - Freiberg Hoffmann, Agustín (2017)
Learning styles and learning strategies describe students’ preferences while they are developing learning activities—grasping and transforming experience—, successfully integrating new and previous information—. 438 college students between 19 and 36 years old participated. Significant differences by sociodemographic and academic variables were verified both in styles and strategies in several dimensions, as well as significant associations between some strategies and the number of technological resources employed by students. Findings report the influence of specific strategies and styles on academic achievement, whereas styles and strategies vary in students according to academic and sociodemographic features. However certain styles and strategies significantly influencing academic achievement in students composing the whole sample were identified.